2020
DOI: 10.5039/agraria.v15i1a5684
|View full text |Cite
|
Sign up to set email alerts
|

Seed production of bush snap beans genotypes in conventional and organic systems

Abstract: Snap beans are one of the ten most consumed vegetables in Brazil, and there are few cultivars available in the Brazilian market. This study aimed to evaluate the seed yield of 20 snap beans genotypes under conventional and organic systems under Brazilian Cerrado conditions. Plant height, number of seeds per pod, weight of 100 seeds and yield were evaluated. For plant height and number of seeds per pod, the 20 genotypes were equal in the conventional cultivation system. In the organic system, the 20 genotypes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…2022. Néri et al (2020) obtained results for seed production in snap bean genotypes in organic and conventional systems, evaluating the identical genotypes used in this study, observed that the Amarelo Japonês, Hab 1, and Tendergreen Improved genotypes had good productive performance in both cultivation systems. In conventional cultivation, Commodore Improved, Festina, and Jade stood out, and in the organic system, Delinel, Hab 39, Improved Gold Wash, Royal Burgundy, Slenderwash, and Tendergreen.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…2022. Néri et al (2020) obtained results for seed production in snap bean genotypes in organic and conventional systems, evaluating the identical genotypes used in this study, observed that the Amarelo Japonês, Hab 1, and Tendergreen Improved genotypes had good productive performance in both cultivation systems. In conventional cultivation, Commodore Improved, Festina, and Jade stood out, and in the organic system, Delinel, Hab 39, Improved Gold Wash, Royal Burgundy, Slenderwash, and Tendergreen.…”
Section: Discussionmentioning
confidence: 58%
“…According to Néri et al (2020), although the introduction of bush cultivars in Brazil is recent, their demand has grown since the 1980s, and the availability of appropriate cultivars is of fundamental importance, both for organic and conventional cultivation. One issue that permeates agricultural production debates is the focus on sustainability, emphasizing organic and agroecological production systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation